2010
DOI: 10.5122/cbirds.2009.0005
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and genetic structure of the Daurian Partridge (Perdix dauuricae) in China, assessed by microsatellite variation

Abstract: The Daurian Partridge (Perdix dauuricae) is a kind of hunting bird with high economic value. Genetic diversity and structure in the Daurian Partridge were studied by analyzing eight microsatellite loci in 23 populations found throughout the range of the species in China. The objectives were to evaluate the consequences on genetic diversity and differentiation of Daurian Partridge populations and to obtain a profound genetic insight for future management decisions and for effective measures to protect and explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
3
1
0
Order By: Relevance
“…We found a considerable amount of genetic diversity within each population, in the range of 1.06 × 10 −3 to 2.31 × 10 −3 ( supplementary table S5, Supplementary Material online), similar to that reported in other bird populations ( Ellegren 2013 ). The genetic diversity was highest in P. dauurica , which is consistent with previous findings of high genetic diversity in this species based on microsatellite variation ( Cao et al 2010 ).…”
Section: Resultssupporting
confidence: 92%
“…We found a considerable amount of genetic diversity within each population, in the range of 1.06 × 10 −3 to 2.31 × 10 −3 ( supplementary table S5, Supplementary Material online), similar to that reported in other bird populations ( Ellegren 2013 ). The genetic diversity was highest in P. dauurica , which is consistent with previous findings of high genetic diversity in this species based on microsatellite variation ( Cao et al 2010 ).…”
Section: Resultssupporting
confidence: 92%
“…Genetic diversity was considerably high in all three species, with the highest in P. daurica, which is consistent with the wider distribution range of this species 122 and the effects of the Tibetan Plateau uplift and environmental changes on its phylogeographic structure 110 . The whole-genome phylogenetic tree indicated that P. perdix is a sister clade to P. dauurica, and P.…”
Section: Discussionsupporting
confidence: 81%
“…We found a considerable amount of genetic diversity within each population, in the range of 1.06 x 10 -3 to 2.31 x 10 -3 (Supplementary Table 5), similar to that reported in other bird populations 121 . The genetic diversity was highest in P. daurica, which is consistent with previous findings of high genetic diversity based on microsatellite variation 122 , possibly due to the wider distribution range of this species.…”
Section: Population-scale Sequencingsupporting
confidence: 91%
“…The microsatellite results also indicated that E. jankowskii had a higher degree of genetic diversity than all passerines birds (H e = 0.24-0.59), which were listed in the article of Jamieson et al (2006), and also higher than N. nippon (H e = 0.50, H o = 0.47) (He 2007), and M. palustris sinensis (H e = 0.53, H o = 0.38) (Zhao 2012). The observed heterozygosity of E. jankowskii was higher than Gallus gallus (H o = 0.37-0.41) and Perdix dauuricae (H o = 0.58), but the expected heterozygosity of E. jankowskii was a little lower than Gallus gallus (H e = 0.72-0.77) and Perdix dauuricae (H e = 0.72) (Cao et al 2010;Masroor et al 2012). It is well established that decreases in genetic variation may reduce fitness and adaptability (Allentoft and O'Brien 2010).…”
Section: High-level Genetic Diversity and Inbreedingmentioning
confidence: 96%